PKM Entrepreneurship in Goat Cultivation in Building Santri Welfare - Zikri, Ihsan (Communautaire: Journal of Community Service, 2023)
The focus of this study is to evaluate the impact of PKM Entrepreneurial Goat Cultivation on the welfare of students and the growth of Jamiatul Ulum Islamic Boarding School. The purpose of this study is to evaluate the impact and factors that influence the implementation of the Goat Cultivation Entrepreneurship Community Partnership Program (PKM) on the welfare of students and the development of Jamiatul Ulum Islamic Boarding School. This research method will use a qualitative approach with participatory observation techniques and in-depth interviews to collect data on the implementation of PKM Entrepreneurial Goat Cultivation in Jamiatul Ulum Islamic Boarding School, while data analysis is carried out thematically to identify the impact of the program and factors that influence its success. The results showed that the Goat Cultivation Entrepreneurship Community Partnership Program (PKM) had a positive impact on the welfare of students at Jamiatul Ulum Islamic Boarding School, with increased income and economic independence as the main results. Factors that contribute to the success of the program include support from the pesantren, active participation of students, access to resources, and cooperation with external parties. However, challenges such as price fluctuations and the availability of animal feed remain major concerns in maintaining the sustainability of the program. The implications of this study highlight the importance of supporting community partnership programs such as PKM Entrepreneurial Goat Cultivation in Islamic boarding schools to strengthen the local economy and improve the welfare of students.